Application of recurrence plot analysis to characterise whole chamber propagation of atrial fibrillation. (24th May 2021) - Pope, M; Kuklik, P; Briosa E Gala, A; Leo, M; Paisey, J; Mahmoudi, M; Betts, TIMOTH
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Oxford Biomedical Research Centre Introduction: Non-contact charge density mapping allows visualisation of whole chamber propagation during atrial fibrillation (AF). The identification of regions with repetitive or, conversely, more complex patterns of wavefront propagation may provide clues to mechanisms responsible for AF maintenance and lead to improved outcomes from catheter ablation. Our novel mapping approach based on signal recurrence plots has never been applied to whole chamber, bi-atrial recording of atrial fibrillation. Purpose: To apply recurrence analysis to characterise whole chamber bi-atrial AF propagation. Methods: Non-contact dipole signals from left and right atrial maps were obtained during simultaneous bi-atrial charge density mapping of AF. Signals were converted to phase and mean phase coherence calculated for the generation of recurrence distance matrices for the whole chamber and each anatomical region (6x LA and 4x RA) over the 30-second recording duration, where a value of 1 (purple, see figure panel A) represents uniform repetitive conduction, and 0 (red), irregular, non-repetitive activity. Whole chamber and regional mean recurrence values were calculated and correlated with the frequency of wavefronts of localised irregular activation patterns. Results: Maps were obtained prior to ablation in 21 patients (5 paroxysmal (pAF), 16 persistent AF (persAF)) undergoing de-novo catheter ablation procedures. Whole chamber recurrence was higher in patients with pAF (0.40 ± 0.08) than persAF (0.34 ± 0.05), p < 0.0005. There was an inverse correlation between regional recurrence values and the number of localised irregular activations detected (-0.7021, p < 0.0005, figure panel B) with the lateral LA and anterior RA demonstrating the highest recurrence values in each chamber (figure panel C). Conclusion: Use of recurrence distance matrices characterises global AF propagation phenotypes. Regional values are inversely correlated with the frequency of localised irregular activation patterns identified demonstrating an anatomic dependence in the level of AF propagation complexity, greatest in the anterior LA and septal RA. Comparison of strategies targeting regions with maximal vs. minimal values during catheter ablation may define an optimal approach to treatment of persistent AF.